Protection Elicited by Attenuated Live Yersinia pestis Vaccine Strains against Lethal Infection with Virulent Y. pestis - Christopher K. Cote; Sergei S. Biryukov; Christopher P. Klimko; Jennifer L. Shoe; Melissa Hunter; Raysa Rosario-Acevedo; David P. Fetterer; Krishna L. Moody; Joshua R. Meyer; Nathaniel O. Rill; Jennifer L. Dankmeyer; Patricia L. Worsham; et al. (Vaccines, 2021)
The etiologic agent of plague, Yersinia pestis, is a globally distributed pathogen which poses both a natural and adversarial threat. Due largely to the rapid course and high mortality of pneumonic plague, vaccines are greatly needed. Two-component protein vaccines have been unreliable and potentially vulnerable to vaccine resistance. We evaluated the safety and efficacy of eight live Y. pestis strains derived from virulent strains CO92 or KIM6+ and mutated in one or more virulence-associated gene(s) or cured of plasmid pPst. Stringent, single-dose vaccination allowed down-selection of the two safest and most protective vaccine candidates, CO92 mutants pgm- pPst- and ΔyscN. Both completely protected BALB/c mice against subcutaneous and aerosol challenge with Y. pestis. Strain CD-1 outbred mice were more resistant to bubonic (but not pneumonic) plague than BALB/c mice, but the vaccines elicited partial protection of CD-1 mice against aerosol challenge, while providing full protection against subcutaneous challenge. A ΔyscN mutant of the nonencapsulated C12 strain was expected to display antigens previously concealed by the capsule. C12 ΔyscN elicited negligible titers to F1 but comparable antibody levels to whole killed bacteria, as did CO92 ΔyscN. Although one dose of C12 ΔyscN was not protective, vaccination with two doses of either CO92 ΔyscN, or a combination of the ΔyscN mutants of C12 and CO92, protected optimally against lethal bubonic or pneumonic plague. Protection against encapsulated Y. pestis required inclusion of F1 in the vaccine and was associated with high anti-F1 titers.